Recruitment and Retention of the Rural Podiatry Workforce in Aotearoa New Zealand: A Qualitative Descriptive Study of Podiatrist Perceptions - Beeler, Erin; Brenton-Rule, Angela; Carroll, Matthew (Springer Science and Business Media LLC, 2022)
Background Past research into the Aotearoa New Zealand (NZ) podiatry workforce has indicated a shortage of podiatrists, particularly in rural NZ. However, there has been no research investigating the characteristics of the NZ rural podiatry workforce. This study aimed to explore the factors which contribute to recruitment and retention of primary care podiatrists in rural NZ. Methods A qualitative descriptive approach was implemented for data collection and analysis. Semi-structured interviews were conducted with 15 podiatrists who currently, or previously, worked in a rural podiatry practice. Manifest content analysis was used to analyse participant’s responses. A deductive approach was used where data were identified and coded according to predetermined themes from the literature. Results Four themes that influenced recruitment and retention were derived from the interviews: (1) professional factors, (2) economic factors, (3) social factors, and (4) external factors. Interviews revealed that clinical inexperience, a sole practice environment, professional and social isolation, and workload pressures combined to affect recruitment and retention. Strong community bonds, family ties, and a rural background were crucial to thrive in the rural setting. Conclusion A sustainable rural podiatry workforce is required to reduce health disparities that exist in NZ rural communities. The study identified that most practitioners entered the rural workforce into self-employed positions, often shortly following graduation from university. They soon reported feelings of professional isolation due to limited support networks. Practitioners established in the rural workforce noted significant workload stresses. Stresses stemming from an inability to source locums, take time away from work, or recruit new staff to fill vacant positions. Research examining support mechanisms for inexperienced practitioners and targeted strategies to grow the rural workforce and reduce attrition is required.
Keywords: Podiatry; Rural workforce; Workforce recruitment; Workforce retention